INFLUENCE OF TWIST TECHNOLOGY BY METHOD OF DOUBLE TORSION ON FORMATION OF RESIDUAL TORSIONS AND STRAIGHTNESS OF METAL CORD - V. P. Fetisov; B. A. Biryukov (Литьë и металлургия)
The purpose of the present work is research of influence of the technological factors, changing the elasticplastic state of twisted product, on stability within time of residual torsions and straightness of metal cord.